Protic Ionic Liquids‐Based Crosslinked Polymer Electrolytes: A New Class of Solid Electrolytes for Energy Storage Devices. Issue 11 (29th September 2020) - Stettner, Timo; Lingua, Gabriele; Falco, Marisa; Balducci, Andrea; Gerbaldi, Claudio
Abstract : Herein, the preparation of an innovative crosslinked polymer electrolyte (PEO_HPyr) encompassing protic ionic liquids (PILs) displaying high ionic conductivity, wide thermal, and electrochemical stability is reported, thus suitable for use in safe energy storage devices. The first example of an all‐solid‐state electrochemical double layer capacitor (EDLC) containing a PEO_HPyr‐based electrolyte is presented, which shows high performance at ambient temperature and exceptional stability. Furthermore, the first example of a PIL‐based lab‐scale lithium‐metal cell with lithium iron phosphate cathodes is also presented, which provides almost full capacity (i.e., 150 mAh g −1 at C/20) and highly reversible cycling at ambient conditions and different current rates. The excellent results obtained clearly demonstrate that PIL‐based crosslinked polymer electrolytes represent a new and very interesting class of solid electrolytes for energy storage devices. Abstract : Herein, the preparation of an innovative, crosslinked polymer electrolyte (PEO_HPyr) encompassing protic ionic liquids displaying high conductivity, thermal, and electrochemical stability is reported. The first examples of all‐solid‐state electrochemical double layer capacitors as well as a lithium‐metal cells with lithium iron phosphate cathodes containing PEO_HPyr are presented. It is shown that both devices display high performance and stability at room temperature.